Implementing Canada's first national virtual phone based overdose prevention service: lessons learned from creating the National Overdose Response Service (NORS) - William Rioux; Pamela Taplay; Lisa Morris-Miller; S. Monty Ghosh (BMC, 2024)
Abstract The opioid epidemic remains one of the largest public health crises in North America to date. While there have been many diverse strategies developed to reduce the harms associated with substance use, these are primarily concentrated within a few large urban centers. As a result, there have been increased calls for equitable access to harm reduction services for those who cannot or choose not to access in-person harm reduction services. In December 2020, Canada's National Overdose Response Service (NORS) a telephone based overdose response hotline and virtual supervised consumption service, was established in collaboration with various agencies and people with lived and living experience of substance use (PWLLE) across Canada to expand access to harm reduction services using novel Opioid Response Technology. In this manuscript we explore the lessons learned from the establishment and continued operation of the service exploring topics related to the initial establishment of the service, securing a phone line, routing technology, EMS dispatch solutions, peer and volunteer recruitment, legal and ethical support, policy and procedure development, securing funding, and marketing. Furthermore, we detail how this service has grown and changed in response to the various needs of service users.